2019
DOI: 10.3390/ijms20102561
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Thermostability, Organic Solvent, and pH Stability in Geobacillus zalihae HT1 and Its Mutant by Calcium Ion

Abstract: Thermostable T1 lipase from Geobacillus zalihae has been crystallized using counter-diffusion method under space and Earth conditions. The comparison of the three-dimensional structures from both crystallized proteins show differences in the formation of hydrogen bond and ion interactions. Hydrogen bond and ion interaction are important in the stabilization of protein structure towards extreme temperature and organic solvents. In this study, the differences of hydrogen bond interactions at position Asp43, Thr1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…The 5M mutant lipase derived from genetically modified of T1 lipase Geobacillus zalihae consists of 388 amino acids with a molecular weight of 43 kDa. This lipase has five mutations (D43E, T118N, E226D, E250L, and N304E) which have been genetically modified based on the comparison of earth-and space-grown T1 lipase structures [19,20]. This mutant lipase showed similar characteristics in temperature and pH optimum as wild-type T1 lipase, which optimally active at temperature 70˚C and pH 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5M mutant lipase derived from genetically modified of T1 lipase Geobacillus zalihae consists of 388 amino acids with a molecular weight of 43 kDa. This lipase has five mutations (D43E, T118N, E226D, E250L, and N304E) which have been genetically modified based on the comparison of earth-and space-grown T1 lipase structures [19,20]. This mutant lipase showed similar characteristics in temperature and pH optimum as wild-type T1 lipase, which optimally active at temperature 70˚C and pH 9.…”
Section: Introductionmentioning
confidence: 99%
“…However, the comparison of thermostability with its parent lipase indicates that 5M lipase has a low tolerance against high temperature based on the half-life study, and melting point analysis. Analysis of the model structure of 5M lipase suggests that the number of molecular interactions such as hydrogen bonds and ion interactions have decreased due to the mutations [20]. Thus, subsequent study has been conducted to solve the three-dimensional structure of 5M lipase and revealed the factor contributes to the decrease in lipase stability using the crystal structure of 5M lipase.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, biochemical characterization of wildtype HT1 lipase has been conducted across a wide range of parameters, including temperature, pH, metal ions, organic solvents and thermostability [ 16 ]. In terms of targeted mutations, there was a shift in optimum temperature for E226D, E250L and N304E in comparison to wildtype HT1 [ 16 ]. The change in optimum temperature was also observed in Y224C and Y224P from thermophilic lipase from Geobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of mutated HT1 lipases with previously characterized wildtype HT1 lipase has revealed that mutants in the form of D43E, E226D, E250L and N304E have a longer half-life and higher melting temperature ( Table 5 ). The wildtype HT1 had a half-life time of 540, 85 and 16 min at 60, 70, and 80 °C, respectively, with a melting temperature at 70.9 °C [ 16 ]. A previous study by Syal et al [ 24 ] demonstrated that YLIPL1 and YLIP9L1Bp3 lipases exhibited better thermostability compared to their wildtype, YLIP9 lipase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation